2020
DOI: 10.3390/ani10111970
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of Turkish Indigenous Donkey Populations Determined by Mitochondrial DNA D-loop Region

Abstract: In this study, to analyze the mtDNA D-loop region and the origin of the maternal lineages of 16 different donkey populations, and to assess the domestication of Turkish indigenous donkeys in seven geographical regions, we investigated the DNA sequences of the D-loop region of 315 indigenous donkeys from Turkey. A total of 54 haplotypes, resulting from 35 polymorphic regions (27 parsimoniously informative and 6 singleton sites), were defined. Twenty-eight of these haplotypes are unique (51.85%), and 26 are shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The mtDNA genome of donkeys is 16 670 bp, of which the D-loop region is 1 207 bp (Xu et al, 1996). As reported in previous genetic studies on donkeys (Lopez et al, 2005;Ma et al, 2020;Ozkan Unal et al, 2020), the D-loop region of ancestral mtDNA supplies adequate information to assess genetic variation, evolutionary relationships, and matrilineal genetic origins.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The mtDNA genome of donkeys is 16 670 bp, of which the D-loop region is 1 207 bp (Xu et al, 1996). As reported in previous genetic studies on donkeys (Lopez et al, 2005;Ma et al, 2020;Ozkan Unal et al, 2020), the D-loop region of ancestral mtDNA supplies adequate information to assess genetic variation, evolutionary relationships, and matrilineal genetic origins.…”
Section: Discussionmentioning
confidence: 79%
“…DNAsp v6 (Rozas et al, 2017) was used to calculate the nucleotide diversity, polymorphic sites, and haplotype diversity of the most variable region in the HGD mtDNA D-loop region. Genetic relationships among populations were determined using median-joining networks (MJN) using Network v.10.1.0.0 software (Bandelt et al, 1999), the MJN was constructed from 11 haplotypes found in this study and 60 reference sequences found previously (Ozkan Unal et al, 2020;Xia et al, 2019), the 15 sequences including Hap4,Hap6,Hap7,and Hap10,Hap12,Hap16,Hap18,Hap20,Hap22,Hap23,Hap24,Hap25,Hap26,Hap27, Hap29 belonged to Clade I. Reference mtDNA D-loop region sequences of wild and domestic donkey were obtained from GenBank and used as comparators of HGDs to build phylogenetic trees and speculate their origin (Han et al, 2014;Ivankovic et al, 2002;Kimura et al, 2011;Oakenfull et al, 2000;Ozkan Unal et al, 2020).…”
Section: Sequence Assembly and Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…MtDNA contains a non-coding control region, also called the displacement-loop region (Dloop) [23]. Previous studies of donkey mtDNA D-loop (control region) sequences depicted the genetic relationships and origin of worldwide modern donkey breeds well [19,[24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Turkish indigenous donkey Turkey [50] The Huaibei Grey donkey mitochondrial genome is 16,617 bp long and contains 37 genes, including 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes [19]. Phylogenetic analysis of 25 Equidae species' complete mitochondrial genomes revealed that the Huaibei Grey donkey is closely related to other domestic donkey breeds, forming a distinct clade.…”
mentioning
confidence: 99%